Immunomodulatory effect of tea saponin in immune T-cells and T-lymphoma cells via regulation of Th1, Th2 immune response and MAPK/ERK2 signaling pathway. (June 2014) - Bhardwaj, Jyoti; Chaudhary, Narendra; Seo, Hyo-Jin; Kim, Min-Yong; Shin, Tai-Sun; Kim, Jong-Deog
Abstract The anti-cancer activity of saponins and phenolic compounds present in green tea was previously reported. However, the immunomodulatory and adjuvanticity activity of tea saponin has never been studied. In this study, we investigated the immunomodulatory effect of tea saponin in T-lymphocytes and EL4 cells via regulation of cytokine response and mitogen-activated protein kinases (MAPK) signaling pathway. Quantitative analysis of mRNA expression level of cytokines were performed by reverse transcription polymerase chain reaction following stimulation with tea saponin, ovalbumin (OVA) alone or tea saponin in combination with OVA. Tea saponin inhibited the proliferation of EL4 cells measured in a dose-dependent manner. No cytotoxicity effect of tea saponin was detected in T-lymphocytes; rather, tea saponin enhanced the proliferation of T-lymphocytes. Tea saponin with OVA increased the expression of interleukin (IL)-1, IL-2, IL-12, interferon-γ and tumor necrosis factor (TNF)-α and decreased the expression level of IL-10 and IL-8 in T-lymphocytes. Furthermore, tea saponin, in the presence of OVA, downregulated the MAPK signaling pathway via inhibition of IL-4, IL-8 and nuclear factor kappaB (NF-κB) in EL4 cells. Th1 cytokines enhancer and Th2 cytokines and NF-κB inhibitor, tea saponin can markedly inhibit the proliferation and invasiveness of T-lymphoma (EL4) cells, possibly due to TNF-α- and NF-κB-mediated regulation of MAPK signaling pathway.